Effect of Maltodextrin on Glass Transition Temperature and Water Activity of Production Banana Flake - Wilai Sonthipermpoon; Thongchai Suwonsichon; Sakchai Wittaya-areekul; Phaisan Wuttijumnong (Agriculture and Natural Resources, 2006)
Glass transition temperature (Tg) has been identified as a critical factor for predicting the quality of foodstuff during processing or storage. Maltodextrin DE 10 at concentrations of 0.9, 1.8, and 2.7% of banana pulp were added to banana pulp to increase the Tg of banana flake. Differential scanning colorimetry (DSC) was used to determine the Tg of banana flake as a function of water content. The equilibrium moisture content was measured over different saturated solutions using the gravimetric method at 35°C. The Tg values of banana flake decreased with increasing water activity while increased with increasing percentage of maltodextrin. The Gordon and Taylor model was used to predict Tg of banana flake. The Guggenheim-Anderson-deBor (GAB model) was used to predict water content of banana flake. It was shown that maltodextrin content increased monolayer water (M0) and the Tg of dry solids for banana flake.